Relasi antara Prinsip Visual Barat dan Fengshui pada Desain Logo - Fenny Ng; Priyanto Sunarto; Naomi Haswanto (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2011)
Nowadays, the integrations between Western principles of visual art with principles of Feng Shui in logo designs can easily be found in Indonesia. Principles of Feng Shui, often called as Feng Sui or Hong Sui, is an ancient Chinese way of thinking that emphasize in environment organization. Principles of Feng Shui's four key points are to produce a positive Qi energy, to maintain stability among Yin and Yang, to produce a productive cycle Wu Xing (Five Elements), and to represent the symbolism from Chinese culture. The purpose of this research is to establish an understanding on the relationship between Western principles of visual art and principles of Feng Shui in logo designs, like the similarities on the way of reading logo as well as the differences. Logo designs were analyzed, described, and explained using Western principles of visual art and principles of Feng Shui's four key points into three sections, which are visual elements, logo composition, and logo interpretation. This research used the qualitative method with descriptive analysis. The data were collected through several methods, such as interviews and literature reviews. The four stages of analysis procedure are description, formal analysis, interpretation, and evaluation or judgement. Upon completion, there are three findings. First, the way of reading a logo design using the Western principles of visual art is simpler and straightforward than the principles of Feng Shui. Second, several relationships among the two principles were found in visual elements, logo composition, and logo interpretation. Third, the integrations between Western principles of visual art with principles of Feng Shui in a logo design represents its ideologies as well as the 'shield' to protect the company from any harm.